2008
DOI: 10.1080/00365520802321212
|View full text |Cite
|
Sign up to set email alerts
|

Altered bile acid metabolism in patients with constipation-predominant irritable bowel syndrome and functional constipation

Abstract: Patients with IBS-C and FC have marked changes in bile acid synthesis in relation to colonic transit. The diurnal rhythm is altered in the slow transit colon when there is no C4 peak at lunchtime. Alterations in bile acid metabolism may be implicated in the pathophysiology of constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 8 publications
0
45
0
1
Order By: Relevance
“…Walters et al (113) provided evidence that impaired feedback inhibition of bile acid synthesis by the ileal hormone FGF-19 plays a role in bile acid-associated diarrhea. Conversely, patients with C-IBS and functional constipation had altered diurnal rhythm with no serum 7␣C4 peak at lunchtime (1). These data might suggest that alterations in genes that regulate bile acid metabolism and feedback may contribute to abnormal bowel pattern and symptoms in IBS.…”
Section: Genetic Predisposition To Bile Acid Malabsorption In Ibsmentioning
confidence: 83%
“…Walters et al (113) provided evidence that impaired feedback inhibition of bile acid synthesis by the ileal hormone FGF-19 plays a role in bile acid-associated diarrhea. Conversely, patients with C-IBS and functional constipation had altered diurnal rhythm with no serum 7␣C4 peak at lunchtime (1). These data might suggest that alterations in genes that regulate bile acid metabolism and feedback may contribute to abnormal bowel pattern and symptoms in IBS.…”
Section: Genetic Predisposition To Bile Acid Malabsorption In Ibsmentioning
confidence: 83%
“…Several recent studies have demonstrated bile acid malabsorption in a subset of patients with IBS (1,29,93,192). Furthermore, reduced ileal absorption and excess of bile acid in the colon can lead to acceleration of colonic transit by stimulating motility and secretion (8,109).…”
Section: Microbiota and Enteric Sensorimotor Functionmentioning
confidence: 99%
“…In another recent study, the normal lunchtime increase in C4 levels was not detected in 82% of functional constipation and irritable bowel syndrome constipation (IBS-C) patients with delayed colonic transit compared with 17% of those with normal transit (p < 0.001). The authors concluded that alterations in diurnal bile acid metabolism might play a role in the pathogenesis of constipation [10].…”
Section: How Might Bile Acids Be Related To Constipation?mentioning
confidence: 99%